Evaluation of non-surgical methods in treatment of pediatric liver cyst hydatid (Annals of Medical Research, 2021)
Aim: Hydatid cyst is a zoonotic infestation caused by helminthes of the Echinococcus genus and humans are intermediate hosts infected with the contaminated fresh food or water. The cases in Turkey are confined to Eastern Anatolia region. Evaluating the prevalence, symptoms and signs of hydatid cysts along with the treatment procedures and response in pediatric cases are vital for better diagnostic and treatment approaches in children.Material nad Methods: The study was conducted retrospectively with a total of 27 children diagnosed with hydatid cyst admitted to Research and Education Hospital of Kafkas University Medical School, Turkey in 2016 and 2019. Results: The mean age of 27 cases reported here was 11.59±4.95. Liver involvement was observed in all of patients reported here and all patients were seropositive. Ten patients underwent Puncture Aspiration Injection Re-aspiration procedure and 17 patients did not undergo. After the Puncture Aspiration Injection Re-aspiration treatment, there was an improvement in all patients for the marker levels. Conclusion: We think that Puncture Aspiration Injection Re-aspiration is superior to non-surgical medical treatment in pediatric patients.